Applying Neuro-Fuzzy Model in Indoor Comfort Microclimate Control - Suliman A.; Uskenbayeva R.; Altayeva A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Climate control; Climate models; Control systems; Energy utilization; Fuzzy inference; Fuzzy neural networks; Office buildings; Predictive analytics; Comfort temperatures; Commercial building; Hardware and software; Indoor environment; Indoor temperature; Management strategies; Microclimate control; Neuro-Fuzzy model; HVAC